KOMODIFIKASI DRAMATARI “CAK RAMAYANA” DESA SINGAPADU DALAM INDUSTRI PARIWISATA - Lestari, Sri Dwi (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 01, Juli 2014DO - 10.24843/JUMPA.2014.v01.i01.p09)
Tourism development causes commodification on several cultural components. One of them is commodification of Cak Ramayana dance drama in Singapadu village. The performance of Cak Ramayana dance drama by dance groups from Singapadu nowadays are performed routinly as a show for tourists. This article analysis the forms of commodifications of Cak Ramayana dance drama of Singapadu village, factors affecting the commodification, and the effects of the commodification to the Singapadu people. Data for the article were collected through interview and document study. They were analyzed by commodification theory and theory of social change. The article concludes that the forms of commodification Cak Ramayana dance drama involved the commodification of production, consumption and distribution, while the effect of commodification included two things. The first one is social economy effect, such as the effect of the sekaa’s income, enhancement of employment oppurtunity, and the other is social cultural effect, such as a mean of binding community citizens formally, preservation cultural and arts and decrease of aesthetic quality of Cak Ramayana dance drama.